Wave climate trends and breakpoints during the Atlantic Multidecadal Oscillation (AMO) in southern Brazil (Ocean and Coastal Research, 2022)
Understanding how wave climate variability and its trends change over time are crucial analyses required to mitigate potential wave-induced impacts and adapt coastal areas to such effects. The long-term trends and breakpoints of the wave energy flux (WEF) and its relationship with teleconnection patterns in southern Brazil were studied using ERA-5 wave reanalysis with validation using a waverider. We determined that the interannual mean WEF (WEFm) and extreme WEF (WEF98) that reaches the southern Brazil have increased over the past four decades, with a increment of 0.063 and 0.17 kW/m/year, respectively 0.63 and 0.29% per year. By the Muggeo method we determined that subperiods with increasing WEFm trends are related to the SSE and SSW quadrants and that these are also the most energetic ones and with the highest annual increment rates of WEFm and WEF98. Our results also suggest that the positive trends observed in interannual WEF values are likely related to the long term transition of cold to warm Atlantic Multidecadal Oscillation (AMO) phase in the western South Atlantic Ocean. From a coastal risk perspective, it is important to understand the relationship between climatic indices and the wave climate to support long-term coastal management policies.